Corrosion behavior of newly developed heat treated 10Mn-2Ni-3.5Cr-1.5Cu alloy - Kumar S.; Singh R.B. (My University, 2025)
A new cast iron alloy of 10Mn-2Ni-3.5Cr-1.5Cu is developed through casting route. The experiments are carried out to investigate the effect of heat treatment on microstructure, hardness and corrosion behavior of the newly developed 10Mn-2Ni-3.5Cr-1.5Cu alloy. Alloy 10Mn-2Ni-3.5Cr-1.5Cu is subjected to heat treated at 800 to 950 °C for 1, 3, 5 and 7 h, and cooled in the air at room temperature. The microstructure of the alloy is characterized by optical and scanning electron microscopy at various experimental stages. The microstructure consists of spherical and finer carbides with the austenite matrix. The different phases are investigated by XRD and EDS. Several carbides such as M3C, M5C2 and M7C3 are observed, which are formed with an austenitic matrix. However, the increase in heat treatment temperature/time leads to an increase in the volume fraction of austenite and dissolution of carbides in the matrix. Corrosion study is carried out in the solution of 5% NaCl using the weight loss method for 7 and 30 days. The corrosion rate and hardness are observed to be lower after heat treatment at 900 and 950 °C for 7 h due to the dissolution of carbides. The results show that this alloy has corrosion resistance equivalent to the high-cost Ni-based alloys. Therefore, the present research aims to develop a new low cost cast iron alloy with high corrosion resistance. © 2019 IOP Publishing Ltd.